2001
DOI: 10.1086/323658
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Hereditary Defective Mismatch Repair in a Prospective Series of Unselected Colorectal Carcinomas

Abstract: A comprehensive analysis of somatic and germline mutations related to DNA mismatch-repair (MMR) genes can clarify the prevalence and mechanism of inactivation in colorectal carcinoma (CRC). In the present study, 257 unselected patients referred for CRC resection were examined for evidence of defective DNA MMR. In particular, we sought to determine the frequency of hereditary defects in DNA MMR in this cohort of patients. MMR status was assessed by testing of tumors for the presence or absence of hMLH1, hMSH2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
207
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(220 citation statements)
references
References 44 publications
8
207
3
2
Order By: Relevance
“…1 In colorectal cancers with microsatellite instability, inactivation of the DNA mismatch repair system results either from a somatic biallelic hypermethylation of the MLH1 gene, 2,3 an epigenetic alteration associated with aging, 4 or from a germline alteration of one gene allele of the DNA mismatch repair system followed by the somatic inactivation of the other. 1,5 Heterozygous germline mutations of genes of the DNA mismatch repair system are the cause of the Lynch syndrome or hereditary nonpolyposis colorectal cancer, the most common form of inherited colorectal cancers.…”
mentioning
confidence: 99%
“…1 In colorectal cancers with microsatellite instability, inactivation of the DNA mismatch repair system results either from a somatic biallelic hypermethylation of the MLH1 gene, 2,3 an epigenetic alteration associated with aging, 4 or from a germline alteration of one gene allele of the DNA mismatch repair system followed by the somatic inactivation of the other. 1,5 Heterozygous germline mutations of genes of the DNA mismatch repair system are the cause of the Lynch syndrome or hereditary nonpolyposis colorectal cancer, the most common form of inherited colorectal cancers.…”
mentioning
confidence: 99%
“…Lynch syndrome (Hereditary NonPolyposis Colorectal Cancer (HNPCC)) accounts for about 5% of colorectal cancers and is caused by a germline mutation in one of the mismatch repair (MMR) genes (Aaltonen et al, 1998;Cunningham et al, 2001;Lynch and de la Chapelle, 2003;Hampel et al, 2005;Barnetson et al, 2006). Known MMR genes causing Lynch syndrome are MLH1, PMS2, MSH2, and MSH6.…”
mentioning
confidence: 99%
“…MSI reflects either the presence of a germline mutation in the MMR system or somatic hypermethylation of the promoter region of the MLH1 gene (Cunningham et al, 2001). Patients with a tumour with MSI and somatic hypermethylation of the MLH1 promoter rarely carry a germline mutation in the MMR system, although rare exceptions have been reported.…”
mentioning
confidence: 99%
“…[4][5][6] Conversely, defective hMSH2 or hMSH6 is almost always due to germline mutations. 7 Several investigators have reported that colorectal carcinomas with defective MMR often show distinctive clinicopathologic features including location in the proximal colon, younger patient age, mucinous differentiation, and a host-immune response characterized by a Crohn's-like lymphoid reaction or tumor infiltrating lymphocytes. [8][9][10][11][12][13][14][15][16][17][18][19][20] Serrated colonic polyps (hyperplastic polyps, mixed hyperplastic and adenomatous polyps, and serrated adenomas), particularly right-sided ones, are also associated with defective MMR 2,21 and are regarded as the precursor lesions for colorectal carcinomas with MSI, thus forming the basis of a 'serrated pathway' of colorectal tumorigenesis.…”
mentioning
confidence: 99%